What's In It For Us? Benevolence, National Security, and Digital Surveillance. (6th April 2021) - Degli Esposti, Sara; Ball, Kirstie; Dibb, Sally
Abstract: This article challenges suggestions that citizens should accept digital surveillance technologies (DSTs) and trade their privacy for better security. Drawing on data from nine EU countries, this research shows that citizens' support for DSTs varies not only depending on the way their data are used but also depending on their views of the security agency operating them. Using an institutional trustworthiness lens, this research investigates three DST cases—smart CCTV, smartphone location tracking, and deep packet inspection—that present escalating degrees of privacy risk to citizens. The findings show that the perceived benevolence of security agencies is essential to acceptability in all three cases. For DSTs with greater privacy risk, questions of competence and integrity enter citizens' assessments.